Regulation of ABCG2 through interactions with Alpha-1-Acid Glycoprotein and EMMPRIN - Likar, Sakura (2025)
The human ABCG2 transporter, a member of the ATP-binding cassette (ABC) transporter superfamily, plays a crucial role in the efflux of various substrates, including chemotherapeutic drugs from cells. Its involvement in drug efflux has been extensively associated with multidrug resistance (MDR) in cancer cells, highlighting the pressing need for a deeper understanding of ABCG2 regulation. One way that proteins are regulated is through interactions with other proteins, impacting their function. The thesis investigated the possible role of alpha-1-acid glycoprotein (AAG) as an extracellular acceptor of ABCG2 substrates, therefore accelerating efflux. Secondly, the thesis studied whether extracellular matrix metalloproteinase inducer (EMMPRIN) acts to stabilize ABCG2 and increase its expression or stability. ABCG2:AAG interactions were investigated through functional time- course transport assays using stably transfected HEK293T-sfGFP- ABCG2 cells and rates of efflux were measured and compared. Semiquantitative analysis of HEK293T-sfGFP-ABCG2 cells co- transfected with EMMPRIN were studied for ABCG2:EMMPRIN interactions. Addition of AAG was not found to have increased the rate of mitoxantrone efflux by ABCG2. Co-expression with EMMPRIN did not result in increased ABCG2 expression in whole cell lysates. Though results from experiments were inconclusive in relation to the proposed hypotheses, groundwork has been laid out for future protein biophysical work that enables investigation of ABCG2 protein-protein interactions.